PENGARUH PENDAPATAN DAERAH TERHADAP BELANJA MODAL PADA PEMERINTAH PROVINSI JAWA BARAT - Alawiyah, Rostika; Rachman, Fatwa Rubiar; Nasution, Indra Surya (Publika Citra Media, 2024)
Through improving public services, it can increase the attractiveness of investors to invest. Therefore, the West Java Provincial Government should change the composition of spending, where currently regional spending is used for operational spending, which is less productive than capital spending. The aim of this research is to find out how much influence PAD has on capital expenditure in the Regional Government of West Java Province. The sample used in this research is the 2019–2021 Regional Government Revenue and Expenditure Report, consisting of 27 regencies and cities in West Java Province. The methods used in this research are descriptive and verification. The analysis technique uses simple linear regression analysis and hypothesis testing. Based on the results of the analysis, it shows that the adjusted R2 value is 0.617, which means that local revenue has an influence on capital expenditure by 38%, while 62% is influenced by other factors not mentioned in the research.